The King and I (1956) [videorecording (DVD)] - Lang, Walter, 1898-1972; Kerr, Deborah, 1921-2007; Brynner, Yul; Moreno, Rita; Landon, Margaret, 1903-1993 (Rodgers and Hammerstein collection., 1999)
An English schoolteacher finds herself at odds with the King of Siam when she is hired as the teacher at the royal court in the 1860s.